2006
DOI: 10.1007/s10545-006-0121-6
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme replacement therapy and bony changes in Egyptian paediatric Gaucher disease patients

Abstract: Symptomatic and radiological skeletal disease is common in children with Gaucher disease in Egypt. MRI is the most accurate technique for detecting early skeletal involvement. There was no correlation between severity of skeletal involvement and GBA genotype. ERT was effective in ameliorating radiological manifestations of skeletal disease and achieving complete remission of bone pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 19 publications
5
29
0
Order By: Relevance
“…Fractions 2-5 were enriched in lipid rafts, as indicated by the presence of GM1 ( Figure 3A). In untreated RAW264.7 cells ( Figure 3A), M-CSFR was found to reside primarily in the non-raft part of the cell membrane, with only a small proportion associated with the rafts; likewise, TRAF6 was found almost exclusively outside the rafts, while as previously reported (4), a significant proporan iminosugar inhibitor of GCS, is taken up by glucocerebroside-laden macrophages, thus ameliorating the clinical phenotype of Gaucher disease, as well as improving the osteoporotic bone phenotype (21,22).…”
Section: Introductionsupporting
confidence: 81%
“…Fractions 2-5 were enriched in lipid rafts, as indicated by the presence of GM1 ( Figure 3A). In untreated RAW264.7 cells ( Figure 3A), M-CSFR was found to reside primarily in the non-raft part of the cell membrane, with only a small proportion associated with the rafts; likewise, TRAF6 was found almost exclusively outside the rafts, while as previously reported (4), a significant proporan iminosugar inhibitor of GCS, is taken up by glucocerebroside-laden macrophages, thus ameliorating the clinical phenotype of Gaucher disease, as well as improving the osteoporotic bone phenotype (21,22).…”
Section: Introductionsupporting
confidence: 81%
“…Definitive diagnosis of GD requires a simple blood test for acid b-glucosidase enzyme activity in peripheral blood leukocytes as outlined by Charrow et al [24]. Further recommendations for monitoring guidelines and therapeutic goals have been recently established to guide physicians in the management of Gaucher patients [12,25].…”
Section: Discussionmentioning
confidence: 99%
“…We examined the consequences of failure to make a prompt diagnosis and the patient characteristics that correlated with diagnostic delays (Table III). Diagnosis was made by demonstration of low leukocyte acid b-glucosidase activity and sequencing of the acid b-glucosidase gene as previously described [25]. Severity of GD was determined by volumetric measurement of viscera and MRI and radiologic evaluation of bone marrow and skeleton as previously described [26].…”
Section: Case Series Of Diagnostic Delays and Their Consequencesmentioning
confidence: 99%
“…(17,18) Importantly, it is not known whether osteopenia in GD1 increases the risk of fractures as it does in postmenopausal women. (19) Imiglucerase therapy improves bone mass and bone mineral density (12,13,(20)(21)(22)(23) and studies have shown an apparent decrease in reports of bone pain and bone crises. (23,24) However, it is not known whether imiglucerase treatment decreases the risk of fractures.…”
Section: Introductionmentioning
confidence: 99%